Students as researchers : creating classrooms that matter - Steinberg, Shirley R.; Kincheloe, Joe L. (Falmer Press teachers' library series, 1998)
This book focuses directly on student empowerment through meaningful research. It fills a specific gap in educational literature by making explicit the relationship between teaching method, classroom practice, and the production of knowledge. Drawing on the best of theoretical innovations over the last decade Students as Researchers places them in a living accessible context. With a sound basis in theory, the book is also extremely practical and accessible for students, giving scenarios and examples that can be used to reveal the workings and benefits of research.
Keywords: Action research in education : United States; Critical thinking : Study and teaching : United States; Research : Study and teaching : United States; Education : United States